HIGHER EDUCATION IN THE USA AND UKRAINE: THE SYSTEMS' DIFFERENCES (Pedagogy of Higher and Secondary Education, 2009)
The article is devoted to the analysis of the Ukrainian and American higher education and to the determination of their differences.
Keywords: State University; Private University; Community colleges Junior colleges Technical colleges; Comprehensive colleges Associate degres SAT